Breaking the cancer code: a novel DNA minicircle to disable STAT3 in ovarian cancer cells SKOV3 - Vasilescu, Adina-Gabriela; Vasilescu, Andrei-Mihai; Sima, Livia Elena; Baran, Natalia; Szedlacsek, Ștefan-Eugen (Frontiers in Pharmacology, 2025)
IntroductionOvarian Cancer remains a significant global health concern, with high mortality rates, largely due to late-stage diagnosis and limited treatment options. These extrinsic factors are driven or exacerbated by intrinsic mechanisms such as persistent activation or upregulation of Signal Transducer and Activator of Transcription 3 (STAT3). STAT3 promotes tumor growth, inhibits apoptosis, accelerates angiogenesis and metastasis, facilitates immune evasion, and contributes to chemoresistance. Consequently, STAT3 activation fosters an aggressive ovarian cancer phenotype, contributing to treatment failure, poor prognosis and low survival rates, highlighting the urgent need for novel, safe, effective and affordable STAT3-targeted therapeutic strategies. In this study, we developed a novel double-stranded DNA minicircle (mcDNA) inhibitor, designed to act as a decoy for STAT3, preventing its binding to target gene promoters.MethodsUtilizing the SKOV3 ovarian cancer cell line, we evaluated the effects of our inhibitor in vitro on cell viability through MTS assay, its apoptotic and necrotic effects using flow cytometry and the expression modulation of downstream STAT3-regulated genes, assayed through RT-qPCR and Western blot analysis.ResultsWe demonstrate that anti-STAT3 mcDNA significantly reduces the viability of SKOV3 cells at low nanomolar concentrations, while sparing the control group. The effect observed was dose-dependent. Mechanistically, anti-STAT3 mcDNA induces apoptosis and necrosis in treated cells, also revealing a certain dose-dependency, while also decreasing cell proliferation. Finally, our inhibitor significantly downregulates STAT3-dependent anti-apoptotic genes MCL1 and PIM1.ConclusionThese findings suggest that anti-STAT3 mcDNA is a promising, effective and specific candidate for targeted STAT3 inhibition in SKOV3 ovarian cancer cells, warranting further validation in ovarian cancer, in vivo exploration and potential application in other types of malignancies, where STAT3 acts as an oncogenic factor.